2022
DOI: 10.3389/fdgth.2022.968806
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the validity of digital health literacy instrument for secondary school students in Ghana: The polychoric factor analytic approach

Abstract: The emergence of the coronavirus pandemic resulted in the heightened need for digital health literacy among the youth of school-going age. Despite the relevance of digital health literacy among the general public (including students), it appears the measurement of digital health literacy is still a challenge among researchers. Recently, Dadackinski and colleagues adapted existing digital health literacy measures to fit the COVID-19 situation. Since this development, the instrument has been widely used with few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…This research design was appropriate because this study went through distinct scientific stages from the planning phase through to the estimation of sample size, data collection and the evaluation of the reliability and validity with different statistical tools ( Arafat, 2016a ). Although there happens to be predominant use of a cross-sectional survey design in recent validation studies (see Agormedah et al, 2022 ; Ankomah et al, 2022 ; Quansah et al, 2022b , c ; Srem-Sai et al, 2022 ), emerging knowledge from scholars is that validation study can be considered as a research design since every stage of validation research has scientifically established rudiments that contradicts the fundamental idea of cross-sectional design ( Anthoine et al, 2014 ; Arafat, 2016b ; Arafat et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…This research design was appropriate because this study went through distinct scientific stages from the planning phase through to the estimation of sample size, data collection and the evaluation of the reliability and validity with different statistical tools ( Arafat, 2016a ). Although there happens to be predominant use of a cross-sectional survey design in recent validation studies (see Agormedah et al, 2022 ; Ankomah et al, 2022 ; Quansah et al, 2022b , c ; Srem-Sai et al, 2022 ), emerging knowledge from scholars is that validation study can be considered as a research design since every stage of validation research has scientifically established rudiments that contradicts the fundamental idea of cross-sectional design ( Anthoine et al, 2014 ; Arafat, 2016b ; Arafat et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…After several validations, the COVID‐DHLI with 4 dimensions and 12 items has been found to have a high level of validity. 41 , 42 The dimensions entail information searching, adding self‐generated content, judging the reliability of information searched and determining the relevance of the information searched. Each dimension comprised 4 items measured on a 4‐point Likert scale ranging from 1 (very easy), 2 (easy), 3 (difficult), and 4 (very difficult).…”
Section: Methodsmentioning
confidence: 99%
“…The instrument has 5 subscales and 15 items. Meanwhile, some validation studies [45,47] have confirmed a COVID-19 DHL instrument that includes 4 subscales (information searching, reliability, self-generated content, and relevance) and 12 items (3 on each subscale) with a greater validity [45,47]. Each subscale was measured on 3 levels: 1-sufficient, 2-problematic, and 3-inadequate.…”
Section: Data Collection Instrumentmentioning
confidence: 99%
“…Each subscale was measured on 3 levels: 1-sufficient, 2-problematic, and 3-inadequate. The reliability coefficient values for the newly validated DHL instrument using the McDonald Omega ω method ranged between 0.735 and 0.869, which is considered acceptable with good usability in Ghana [45]. Informationsearching platforms of participants were measured by asking each participant to "indicate how often you currently use these sources of information or otherwise relating to COVID-19".…”
Section: Data Collection Instrumentmentioning
confidence: 99%
See 1 more Smart Citation